The impact of globalization on innovative public procurement: Challenges and opportunities - Otilia Manta; Egla Mansi (Administrative Sciences, 2024)
Incorporating circular economy principles into forward-thinking public procurement strategies enhances sustainability through the promotion of resource efficiency, sustainable sourcing, and extended producer responsibility. This approach not only encourages innovation and collaboration among suppliers but also drives the development of solutions aligned with circular economy goals. The ultimate result is a more cost-effective and environmentally friendly outcome in procurement. This article seeks to investigate the intersection of circular economy principles within the framework of an innovative public procurement system. The study explores the influence of globalization on this innovative public procurement paradigm, addressing both the challenges and opportunities inherent in the process. The study conceptualizes Innovative Public Procurement (IPP) as a strategic approach where public entities acquire goods, services, works, and utilities, emphasizing an optimal balance between price and quality. The central goal is to generate innovative benefits for both entities and society, all while minimizing adverse environmental effects. Employing traditional research methods, including the monographic method, document analysis, and comparison, the study illustrates how public procurement practices can be opened to innovators, including start-ups and innovative SMEs. The findings shed light on the challenges faced by these entities in navigating the procurement landscape, while emphasizing the potential opportunities arising from the synergy between innovative procurement practices and the circular economy. By adopting a holistic perspective that considers the full lifecycle costs and environmental impacts of goods and services, procurement decisions can prioritize options offering superior long-term value. This contributes to the broader transition towards a circular economy, effectively minimizing adverse effects on the environment...
Keywords: 350; circular economy; innovative public procurement; environmental impact; monographicmethod